Therapeutic Role of Inducible Nitric Oxide Synthase Expressing Myeloid-Derived Suppressor Cells in Acetaminophen-Induced Murine Liver Failure - Hsu, Chen-Yu; Lin, Yung-Chang; Chang, Li-Yuan; Huang, Sheng-Kai; Huang, Chien-Hao; Yang, Chan-Keng; Huang, Ching-Tai; Lin, Chun-Yen (Frontiers in Immunology, 2020)
Background: Acetaminophen (APAP) overdose is one of the major etiologies of liver failure. Hepatocyte necrosis induced by toxic metabolites of APAP can activate proinflammatory responses, including elastase-expressing neutrophils, to exacerbate liver injury. Myeloid-derived suppressor cells (MDSCs) increased in inflammation can inhibit proinflammatory responses. Our aim is to investigate the role of MDSC in APAP-induced liver failure and the possible therapeutic application. Methods: BLAB/c mice were injected with a sublethal/lethal dose of APAP as the murine model of liver failure. MDSCs were defined as CD11b+Gr-1+ cells with the ability of T-cell suppression. Results: A sublethal challenge of APAP could increase the intrahepatic MDSC and protect mice against subsequent lethal challenge of APAP, lipopolysaccharide (LPS)/D-galatosamine or concanavalin A. This protection was lost if MDSCs were depleted and inducible nitric oxide synthase (iNOS) was the key molecule in this MDSC-mediated protection. Taking advantage of these observations, different bone marrow-derived MDSCs (BM-MDSCs) were generated. Among different cytokine-treated BM-MDSCs, tumor necrosis factor alpha/LPS-primed MDSCs (TNF-α/LPS MDSCs) had the strongest liver-protection ability after adoptive transfer. Further mechanistic explorations showed, iNOS-expressing TNF-α/LPS MDSCs induced the apoptosis of activated neutrophil and decreased the intrahepatic infiltration of elastase-expressing neutrophil. Moreover, we generated MDSCs from human peripheral blood mononuclear cells (PBMCs) with similar phenotype. Conclusion: We demonstrated the protective role of MDSCs and therapeutic effect of TNF-α/LPS MDSCs in APAP-induced liver failure. MDSC might protect against the APAP-induced liver failure by reducing the intrahepatic infiltration of activated neutrophil to limit inflammation. Therefore, a therapeutic role of MDSCs for APAP-induced liver failure was proposed.